Nomogram to predict primary non-response to infliximab in patients with Crohn's disease: a multicenter study. (12th November 2020) - Ye, Xiao-Qi; Cai, Jing; Yu, Qiao; Cao, Xiao-Cang; Chen, Yan; Rao, Mei-Xin; Chen, Bai-Li; He, Yao; Zeng, Zhi-Rong; Chen, Hao; Lin, Yi-Mou; Cao, Qian; et al.
Abstract: Background: Infliximab (IFX) is effective at inducing and maintaining clinical remission and mucosal healing in patients with Crohn's disease (CD); however, 9%–40% of patients do not respond to primary IFX treatment. This study aimed to construct and validate nomograms to predict IFX response in CD patients. Methods: A total of 343 patients diagnosed with CD who had received IFX induction from four tertiary centers between September 2008 and September 2019 were enrolled in this study and randomly classified into a training cohort ( n  = 240) and a validation cohort ( n  = 103). The primary outcome was primary non-response (PNR) and the secondary outcome was mucosal healing (MH). Nomograms were constructed from the training cohort using multivariate logistic regression. Performance of nomograms was evaluated by area under the receiver-operating characteristic curve (AUC) and calibration curve. The clinical usefulness of nomograms was evaluated by decision-curve analysis. Results: The nomogram for PNR was developed based on four independent predictors: age, C-reactive protein (CRP) at week 2, body mass index, and non-stricturing, non-penetrating behavior (B1). AUC was 0.77 in the training cohort and 0.76 in the validation cohort. The nomogram for MH included four independent factors: baseline Crohn's Disease Endoscopic Index of Severity, CRP at week 2, B1, and disease duration. AUC was 0.79 and 0.72 in the training and validation cohorts, respectively. The two nomograms showed good calibration in both cohorts and were superior to single factors and an existing matrix model. The decision curve indicated the clinical usefulness of the PNR nomogram. Conclusions: We established and validated nomograms for the prediction of PNR to IFX and MH in CD patients. This graphical tool is easy to use and will assist physicians in therapeutic decision-making.